MENTAL INSANITY AS ONE OF BARRIERS OF CRIMINAL RESPOSIBILITY IN THE COMPARATIVE JORDANIAN PENAL LAW - AL - Sweilmeen, Mohammed mousa; Shnikat, Morad mahmoud yousef (European Scientific Journal, ESJ, 2012)
It has been indisputable philologically and judiciary perspective that no to hold a person responsible for an act he committed, even though his action is considered to be a crime according to the law, in case of that person is not capable to recognize his action due to external factor inflicts him or as a reason involve his mental ability.However logic and fairness give society justifications – self – protection and defense – to take measures with which prevent the danger of such people according to article (92) of the Jordanian penal law.The matter of penal obligation’s total obstruction is the soundness of awareness and freedom of choice. In case if one of them or both are missing thus, there will be a reason for its obstruction. As a result, it can be set that awareness loss, or choice is the reason for all penal obligation barriers. Thus, our research is about the criteria or conditions for penal obligation obstruction due to mental insanity. And the rules of mental Insanity in terms of proving it and its effect on legal adaptation involved with criminal act in regard to the mental Insanity relation in the penal contribution and civil liability.